Preputial and scrotal cutaneous mast cell tumors in dogs show no evidence of inherently higher biologic malignancy - Žagar, Žiga; Wehrend, Axel; Schmidt, Jarno M.; Kuehnel-Lawatsch, Sandra; Buehler, Tabea; von Bomhard, Wolf; Kessler, Martin (Frontiers in Veterinary Science, 2025)
Canine genital mast cell tumors (MCTs) have been associated with a poorer prognosis; however, no larger study has focused exclusively on MCTs in this region. This study aimed to retrospectively describe the clinicopathologic aspects and outcomes of dogs with cutaneous preputial and scrotal MCTs and compare the findings to historical data from cutaneous MCTs from other locations. Medical records from 2002 to 2024 from a single institution were reviewed and 91 dogs (35 preputial, 56 scrotal) treated surgically with or without adjuvant therapy and a minimum follow-up of 6 months were included. Tumors were graded according to Patnaik (preputial: 63% grade I, 31% grade II, 6% grade III; scrotal: 41% grade I, 38% grade II, 21% grade III) and Kiupel (preputial: 91% low-grade, 9% high-grade; scrotal: 79% low-grade, 21% high-grade). Histological evaluation of superficial inguinal lymph nodes was performed in 55% of cases (50 dogs); of these, 16% (8/50) showed HN3 metastases. The overall median survival time was not reached and the 1-, 3- and 5-year survival rates were 85%, 67%, and 60%, respectively. On multivariable analysis, Kiupel high-grade and tumor diameter of at least 2 cm were associated with a shorter overall survival time, while HN3 lymph node metastases, aberrant KIT staining pattern, and Ki-67 index >23 were not. This data does not provide evidence of an inherently high biologic aggressiveness of preputial and scrotal MCTs. In the absence of other negative prognostic factors, dogs with preputial and scrotal MCTs have a favorable prognosis.